Design and real-time simulation of an AC voltage regulator based battery charger for large-scale PV-grid energy storage systems - Vavilapalli S.; Subramaniam U.; Padmanaban S.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery storage; Bridge circuits; Electric current regulators; Electric inverters; Energy storage; Fault tolerance; Real time systems; Secondary batteries; Solar cells; Solar energy; Voltage control; Voltage regulators; Battery chargers; Cascaded H-bridge; Power conditioning; PV inverter; Real time simulators; Charging (batteries)